PENGARUH MOTIVASI DAN LINGKUNGAN KERJA YANG BERKELANJUTAN TERHADAP KINERJA KARYAWAN PADA SATUAN PELAYANAN PEMENUHAN GIZI YAYASAN AZMINDO KARYA MANDIRI - Muqit Fadila, Dienda; Nurhasan, Rohimat (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to examine the effect of motivation and a sustainable work environment on employee performance at the nutrition service unit of Azmindo Karya Mandiri Foundation. This research employs a quantitative approach using a verification method. The respondents consist of all employees (n = 100), selected using a census sampling technique. Data were collected through questionnaires and supported by relevant secondary sources. The analysis was conducted using Structural Equation Modeling (PLS-SEM). The results indicate that both motivation and a sustainable work environment have a positive and significant effect on employee performance. Motivation is found to have a more dominant influence compared to the work environment. This study contributes to the human resource management literature by providing empirical evidence in the context of nutrition service organizations, which has been relatively underexplored.